Investigation of carbon nanotube antennas using thin wire integral equations - N. Fichtner; X. Zhou; P. Russer (Advances in Radio Science, 2008)
In this paper the characteristics of small carbon nanotube (CNT) dipole antennas are investigated on the basis of the thin wire Hallén integral equation (IE). A surface impedance model for the CNT is adopted to account for the specific material properties resulting in a modified kernel function for the integral equation. A numerical solution for the IE gives the current distribution along the CNT. From the current distribution the antenna driving point impedance and the antenna efficiency are computed. The presented numerical examples demonstrate the strong dependence of the antenna characteristics on the used material and show the limitations of nanoscale antennas.